2006
DOI: 10.5194/aab-49-434-2006
|View full text |Cite
|
Sign up to set email alerts
|

<i>GHRH/Hae</i>III gene polymorphism and its associations with milk production traits in Polish Black-and-White cattle (short communication)

Abstract: Abstract. The objective of this paper was to evaluate the relationship between the polymorphism of the GHRH and milk production traits of Polish Black-and-White. A total of 881 cows were included in the study. A PCR-RFLP method was used to genotyping. The frequencies of the genotypes and alleles were as follows: 0.0545 for AA, 0.3133 for AB and 0.6322 for BB, and 0.2111 for GHRHA and 0.7889 – GHRHB. There were no significant associations between GHRH/HaeIII polymorphism and milk production traits of the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…According to these authors, the rare AA genotype was significantly associated with the discussed traits (P ≤ 0.01). DYBUS and GRZESIAK (2006) also found that cows with one or two GHRH A alleles might produce milk of a higher fat percentage, although this was not statistically signifi cant. However, a low number of the individuals with the AA genotype strongly limits the conclusions.…”
Section: : a Part Of The Fluorogram Of Intron 2 Of Bovine Ghrh Gene mentioning
confidence: 99%
“…According to these authors, the rare AA genotype was significantly associated with the discussed traits (P ≤ 0.01). DYBUS and GRZESIAK (2006) also found that cows with one or two GHRH A alleles might produce milk of a higher fat percentage, although this was not statistically signifi cant. However, a low number of the individuals with the AA genotype strongly limits the conclusions.…”
Section: : a Part Of The Fluorogram Of Intron 2 Of Bovine Ghrh Gene mentioning
confidence: 99%
“…Contrastly, genotype frequencies of this gene were mostly different for Limousin GG (0.667), AA (0.238) and AG (0.095), Simmental AG (0.529), GG (0.471) and AA (0.000), Pesisir AA (0.604), GG (0.375) and AG (0.021) stated as polymorphic evidences. Dybus & Grzesiak (2006) in their study on the evaluation of the diversity of GHRH gene with milk production in Poland dairy cattle. From that study identified three genotypes and two alleles, by the genotypes of AA (0.0545), AB (0.3133) and BB (0.6322); as well as by the alleles of A (0.2111) and B (0.7889).…”
Section: Genotype and Allele Frequencies Of The Ghrh Genementioning
confidence: 99%
“…Changes in the functional regions of GHR can affect its binding capacity and signalling pathway, and therefore alter the activity of GH in the target tissues (Olenski et al, 2010). Several polymorphisms of bovine GHR were described by Dybus & Grzesiak (2006) and Kmiec et al (2007). The growth promoting and metabolic actions of the GH are generally mediated by insulin-like growth factor I (IGF-I), which is a 70 amino-acid, single-chain polypeptide produced in the liver in response to GH.…”
Section: Introductionmentioning
confidence: 99%